Virtual modelling of solid objects with constraint-based manipulations - Zhong, Yongmin; Yuan, X.; Ma, W.; Shirinzadeh, B. (ACTA Press, 2006)
This paper presents an intuitive approach to precise solid modellingin virtual reality environments. A hierarchically structured modelis established to handle the tasks of object definition, objectcreation, and object rendering with an integrated data structure.Constraints are organized at different levels on different objectsand are embedded in the data structure. A constraint reasoningengine is developed to automatically determine allowable motions forprecise manipulation of virtual objects with online assistance fromconstraints. Examples are presented to demonstrate the advantageof precise solid modelling through constraint-based manipulations invirtual environments.